Os gêmeos afro-brasileiros e o sincretismo religioso: o culto aos gêmeos - entre África e Brasil - N'Dala, Dieudonné Bukasa (2013)
Our objective for this study is to write about the Syncretism Afro Brazilian, particularly, and the syncretism Afro Catholic with the case of Ibeji e saints Cosmas and Damian, particularly. This way we wrote about the twins in Africa first and about the twins in Brazil at the second moment. After this, we made our considerations